2023
DOI: 10.1186/s12889-023-15956-6
|View full text |Cite
|
Sign up to set email alerts
|

Routine health check-ups for adolescents in Mwanza City, Tanzania: stakeholders’ recommendations on its content, venue, and mode of delivery

Abstract: Background Routine adolescent health screening aiming at the detection of unnoticed medical problems may increase awareness among policy makers and contribute to improved health in this population. Research is needed to inform the World Health Organization (WHO) and national health programs to provide evidence-based guidance on whether public health systems should offer comprehensive adolescent health screening, what should be included in different contexts, and how it should be delivered. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Patient and public involvement The intervention was designed following formative research conducted in three African countries between 2019 and 2020. [19][20][21] This formative research revealed that the proposed adolescent health and well-being check-ups are likely to be feasible to implement and acceptable to stakeholders in Ghana, Tanzania and Zimbabwe, and are likely to meet the perceived needs of key stakeholders including adolescents, their parents and key policy makers in the health and education sectors. 22 Further, we showed that the programme is likely to produce a substantial yield of important, previously untreated, treatable conditions.…”
Section: Open Accessmentioning
confidence: 91%
See 1 more Smart Citation
“…Patient and public involvement The intervention was designed following formative research conducted in three African countries between 2019 and 2020. [19][20][21] This formative research revealed that the proposed adolescent health and well-being check-ups are likely to be feasible to implement and acceptable to stakeholders in Ghana, Tanzania and Zimbabwe, and are likely to meet the perceived needs of key stakeholders including adolescents, their parents and key policy makers in the health and education sectors. 22 Further, we showed that the programme is likely to produce a substantial yield of important, previously untreated, treatable conditions.…”
Section: Open Accessmentioning
confidence: 91%
“…Interviews and participatory workshops with adolescents, parents of adolescents and key stakeholders from the ministries of health and education, non-governmental organisations, healthcare workers and teachers found that there was overall support for the introduction of routine health check-ups. [19][20][21] To navigate potential barriers, stakeholders suggested clear messaging, awareness building and sensitisation campaigns to overcome disinterest in preventative healthcare and, in some contexts, mitigate cultural or religious messaging against healthcare engagement. 19…”
Section: Open Accessmentioning
confidence: 99%